Answers

2015-05-16T15:21:53+05:30
a. 2m-3 = 3/10(5m-12)
    2m-3 = 15m-36/10
    10(2m-3) = 15m-36
    20m-30 = 15m-36
    20m - 15m = 30-36
    5m = -6
     m = -6/5

b.  6 (3a+2) - 5 (6a-1) = 3 (a-8) - 7 (5a-6) +9a
     18a+12-30a+5 = 3a-24-35a+42+9a
      -12a+17 = -23a+18
      23a-12a = 18-17
      11a = 1
       a = 1/11

c. 9x+7/2 - (x-(x-2/7) ) = 36
    [9x(2)+7] / 2 - (x-([7x-2/7)) = 36
    [18x+7] / 2 -  (x-7x+2/7) = 36
    [18x+7] / 2 -  (-6x+2/7) = 36
    lcm of 2, 7 is 14
    [18x(7) +7(7) +6x(2)-2(2)] / 7 = 36
    126x+44+12x-4/7 = 36
    138x+40=36×7
    138x = 252 - 40
     138x = 212
     x = 106/69

d. 2 (m-2) - 3 (m-3) = 5 (m-5) - 4 (m-8)
    2m-4-3m+9 = 5m-25-4m+32
    5-m = m + 7
     m+m = 5-7
    2m = -2
    m = -1
    
   
    
1 5 1
thaaankkk uuu.....sweettiieee...:*
:) u r welcome deariee :)
2015-05-16T15:34:07+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
2m-3=\frac{3}{10}(5m -12)\\\\10*(2m-3)=3*(5m-12)\\\\20 m - 30 = 15 m - 36\\\\5m =-6\\\\m=-\frac{6}{5}
========

6 (3 a + 2)  -  5 (6 a - 1) =  3 ( a  - 8) - 7 ( 5 a - 6) + 9 a
18 a + 12  - 30 a + 5 = 3 a - 24 - 35 a + 42 + 9 a
- 12 a + 17 = - 23 a + 18
23 a - 12 a = 18 - 17
11 a = 1
a =  1 / 11

===========
here it is not clear  if the  2 in denominator, has numerator  7  or  9 x + 7 ??
           same way,  it is x-2  or  2 in the numerator for  denominator 7 ?

case 1:

9 x + \frac{7}{2} - (x - (x -\frac{2}{7})) = 36\\\\9 x + \frac{7}{2}-( x - x +\frac{2}{7})  = 36\\\\9 x + \frac{7}{2} -\frac{2}{7} = 36\\\\9 x + \frac{7*7 - 2*2}{14}= 36\\\\9 x + \frac{45}{14} = 36,\ \ \ \ divide\ by\ 9\\\\x = 4- \frac{5}{14}\\\\x =\frac{56- 5}{14}\\\\x = \frac{51}{14}
===========
case 2:

\frac{9 x+7}{2} - ( x  - \frac{x - 2}{7})\\\\=\frac{9 x+7}{2} - (\frac{7x-x + 2}{7})\\\\=\frac{9 x+7}{2} - (\frac{6x + 2}{7})\\\\=\frac{7(9x+7)-2(6x+2)}{2*7}\\\\=\frac{63x+49-12x-4}{14}\\\\=\frac{51x+45}{14}\\\\=\frac{3(17x+15)}{14} 


1 5 1
please click on thanks blue button above
yeah..i did
plzz answer my other questions also sir